Systematic review and meta-analysis of sutures coated with triclosan for the prevention of surgical site infection after elective colorectal surgery according to the PRISMA statement. Issue 35 (August 2016) - Sandini, Marta; Mattavelli, Ilaria; Nespoli, Luca; Uggeri, Fabio; Gianotti, Luca
Abstract: Background: Several randomized clinical trials (RCTs) conducted to evaluate the effect of triclosan-coated suture on surgical site infection (SSI) yield to controversial results. The primary purpose of this systematic review and meta-analysis was to analyze the available RCTs, comparing the effect of triclosan-coated suture with uncoated suture on the incidence of SSI after elective colorectal operations. As secondary endpoint of the analysis, we considered length of hospital stay after surgery. Methods: We performed a systematic literature review through Medline, Embase, Pubmed, Scopus, Ovid, ISI Web of Science, and the Cochrane Controlled Trials Register searching for RCTs published from 1990 to 2015. To conduct these meta-analyses, we followed the guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Study inclusion criteria were as follows: parallel-group RCTs in adult populations reporting the closure of the abdominal wall after elective colorectal operation with triclosan-coated suture or noncoated suture, and reporting the outcomes considered in the meta-analysis. Results: Six trials including 2168 patients (1102 treated and 1066 controls) provided data on SSIs. The overall rate was 11.7% (129/1102) in the triclosan group and 13.4% (143/1066) in the control group (odds ratio 0.81, 95% confidence interval [CI] 0.58–1.13, P  = 0.220). Heterogeneity among studies was moderate ( I 2  = 44.9%). No evidence of publication bias was detectable. Five RCTs (1783 patients; 914 treated and 689 controls) described hospital length of stay with no significant effect (mean difference: −0.02, 95% CI −0.11 to −0.07, P  = 0.668). The I 2 test for heterogeneity was 0% ( P  = 0.836). Moderator analyses showed no significant differences were detected in analyses comparing the suture materials (polydioxanone vs polyglactin). In open-label trials, the odds ratio for SSI risk was 0.62 (95% CI 0.20–1.93, P  = 0.413), 0.77 in single-blind (95% CI 0.31–1.95, P  = 0.583) and 0.85 in double-blind trials (95% CI 0.46–1.54, P  = 0.582). Conclusions: Our findings failed to demonstrate a significant protective effect of triclosan-coated sutures on the occurrence of SSI after elective colorectal resections. Further large RCTs are needed before introducing this technology into clinical practice.